Clinical Knowledge and Practice of “Ketofol” at University of Gondar Comprehensive Specialized Hospital - Woldekidan, Nigist Alemayehu; Mohammed, Ammas Siraj (Frontiers in Medicine, 2021)
Abstract Background: ketamine and propofol in a single -syringe are reported to create an admixture used for balancing cardiorespiratory effects during induction of general anesthesia. The aim of this study is to assess the clinical practice and knowledge of “ketofol” among anesthesia providers. Methods: A cross sectional institutional based study was conducted among anesthesia providers. Data abstracted format was prepared and distributed to senior anesthetist, junior anesthetist postgraduate students, and undergraduate students. The study was conducted from January 1-30, 2019. Descriptive statistics and binary logistic regression were performed for frequency distribution and to determine association, respectively. Result: From a total of 133 participants included in the study majority 88(66.2%) of them were males and had 0-2 years of experience 75(56.9%). More than two third 105(78.9%) of participants have never had seminar or educational session about combined use. Lack of experience 11(8.3%) was the among reasons for not using “ketofol” followed by lack of knowledge 3(2.3%). Most 112(84.2%) of participants prefer ketamine and propofol to be administered one right after the other with separate syringes and the ratio to be 1:2, 64(48.2). There was no significant association observed between socio-demographic and other characteristics, and the practice of “ketofol”. Conclusion: In this study nearly half of participants rated their knowledge at average level and the study identifies there is clinical knowledge and practice gap among anesthesia providers working in UOGCSH. Preparing educational session regarding “ketofol” for addressing identified barriers is among the recommendations forwarded to UOGCSH. Keywords: Anesthesia, Ketamine, propofol, Practice, Knowledge